STRUKTUR GERAK TARI GONG GAMAL SUKU DAYAK SAWE KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Januarti, Yohana; Fretisari, Imma; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research is based on the desire of researcher to analyze the motion contained in Gong Gamal Dance of Sawe Dayak Tribe. The purpose of this research is to describe the structure of Gong Gamal Dance movement with pictures to be understood more clearly. The method used is descriptive method with qualitative form and using ethnocoreology approach, with data source in the form of Gong Gamal Dance which is exhibited by resource persons and artists of Gong Gamal Dance namely Lukas Sadarung, Robertus apon, and Lusia Siti who know about the movement of Gong Gamal Dance in Sekadau Hulu Subdistrict of Sekadau Regency. The research data in the form of movement structure of Gong Gamal Dance, which is related of the art in the dance perfomance which are the beginning, the contents, and the end. Data collection techiques are observation techniques. Technique examination of data validity in the form of extension technique of observation and technique of triangulation. The reult of research are: 1) Analysis of movement structure of Gong Gamal Dance with two motion variation where one variance is divided into two, male and female motion is motion 1 a, motion 1 b, motion 2 a, and 2 b are analyzed based on motion motifs, motion phrases, motion sentences, and clusters of motion. 2) Gong Dynasty Gamal Dance Notation. 3) Design of research results with curriculum applicable asteaching mterials Art and Cultural Arts (dance) with learning implementation plan (RPP) in high school students.Keywords: Motion Structure, Gong Gamal Dance, Dayak Sawe.